Conflict or synergy? Understanding interaction between municipalities and village commons (regole) in polycentric governance of mountain areas in the Veneto Region, Italy. Issue 2 (August 2016) - Favero, Matteo; Gatto, Paola; Deutsch, Nathan; Pettenella, Davide
A particular challenge for mountainous areas in Italy is the definition of suitable governance models for local resources. Several solutions have been proposed over time, resulting in the co-existence of a number of decision-making centers. A crucial role is played by municipalities, but, in recent years, village commons – regola (singular) / regole (plural) in the local language – have been re-constituted as institutions with local power. In this dynamic context, little is known on how municipalities and regole interact. This paper aims at improving the understanding of local governance of mountain areas in the Veneto Region, from the viewpoint of municipalities, which represent the political, legal and administrative authority. The analysis is grounded in the polycentric governance literature, especially crucial in drawing attention to level and extent of cooperation, trustworthiness, mutual learning and effort for adaptation. Tensions, conflicts and conflict-resolution mechanisms were also assessed. We carried out a survey of 14 municipalities containing regole within their administrative jurisdictions. The results of our work provide evidence that this relationship is mostly a synergistic one. Municipalities showed adaptive capacity in mirroring values and views of the regole and proved willing to share responsibilities. Their decisions were formulated whilst taking into account the need for creating the appropriate linkages with local communities. Where conflicts or discontent have emerged, they have been mostly resolved, or considered as reflecting a need for greater coordination. This outcome can be looked upon as a local polycentric governance innovation that so far has only partially received policy support at the regional level. We conclude that municipalities will continue to play a central role in regulation of local-level socio-economic dynamics, remaining the institutional reference point for mountainous areas in the Veneto Region.